MOLECULAR DETECTION OF GENE RESISTANT TO VARIOUS INSECTICIDES IN Aedes aegypti AT BANYUWANGI EAST JAVA USING POLYMERASE CHAIN REACTION - Yudhana, Aditya; Praja, Ratih Novita; Yunita, Maya Nurwartanti (Jurnal Kedokteran Hewan, 2018)
The purpose of this study was to determine the type of insecticides which Aedes aegypti mosquitoes are resistant to, so that other susceptibleinsecticides still can be used. The study was a cross sectional epidemiological study with cluster sampling in Sub-district Wongsorejo,Banyuwangi, Muncar, Tegaldlimo, Kalibaru which is considered sufficient to represent Banyuwangi Regency. Mosquito samples appropriate tothe characteristics were isolated and tested for insecticide-resistance primer namely voltage gated sodium channel (VGSC) to determine thespecific resistance expressed in mosquitoes. The result of resistance test using WHO standard method showed that Aedes aegypti mosquito fromBanyuwangi Regency were resistant to cypermethrin 0.25% and malathion 0.8%. There was a VGSC coding gene with 250 bp band detectedusing polymerase chain reaction (PCR) technique which was associated with the resistance of Aedes aegypti mosquitoes in Banyuwangi Regencyto organophosphate insecticides (malathione) and pyrethroid insecticides (cypermethrin).